Situation report on Nepal’s agrifood systems: July 2024 - Palikhe, A.; Adhikari, Madan; Gupta, S.; Maharjan, N.K.; Kumar, Avinash; Minot, Nicholas; Koirala, P.; Krupnik, Timothy J. (CSISA, 2024)
In June 2024, the national wage rate index and remittance inflows to Nepal increased, while the Consumer Price Index (CPI) declined, improving the purchasing power of lower-income households. The lower CPI was partly due to falling prices for ghee and edible oil, making nutritious options more affordable for both rural and urban households. However, increased prices for cereals, certain fruits, vegetables eggs, fish, and meat have negatively affected these households. Additionally, rising petroleum prices have increased production costs for farmers, potentially leading to higher food prices in the future. The Nepal Living Standard Survey IV (2022-23) reveals significant shifts in Nepal's agricultural practices, highlighting a decline in the number of agriculture households and average land holding, changes in crop cultivation, and a reduction in livestock farming. A significant gender wage gap persists in Nepal's agricultural sector, with women earning less than men, particularly in Banke district, while Bardia and Dang districts show gender parity in the Feed the Future (FtF) Zone of Influence (ZoI). This highlights ongoing gender inequality and the urgent need for initiatives to promote equity and improve the livelihoods of female agricultural workers.